THE EFFECTIVENESS OF USING ANTICIPATION GUIDE STRATEGY IN READING SKILL AT THE ELEVENTH GRADE STUDENTS’ OF SMAN 5 BULUKUMBA - Reski, Reski; Saiful; Mahmudah, Dzur Rif’ah (FKIP Unismuh Makassar, 2024)
This research aim to found the effectiveness of using anticipation guide on students reading comprehension by conducting pre-experimental research at the eleventh grade of SMA Negeri 5 Bulukumba as the research location and taking sample with a total of 270 eleventh grade students, while the sample used was 25 students the process of data collection using pre-test and post-test by using SPSS Vol 25. The results of this study found that the use of anticipation guide strategy in the learning process to improve students reading comprehension that considered effective based on the data obtained where the mean score of the pre-test in interpretative and literal 63.12 became 90.64 in post-test. It can be seen that the mean score of the post test is higher than the mean score of pre-test. Based on these results, it can be concluded that anticipation guide strategy is effective in improving students’ reading comprehension.